Political Communication, Freedom of Expression, and Ethics - Kavoğlu, Samet; Salar, Meryem (IGI Global, 2020)
The chapter addresses the implementation of “binding group decision” problematically. According to the study, this implementation is a restrictive issue for the discourses and actions of the members of the parliament who are assigned with the duty of representation of the nation and entitled with privileges within the context of freedom of expression. In this context, the legal legislation and bylaws of the political parties with groups in the Grand National Assembly of Turkey (TBMM) and internal regulations are analyzed within the context of restrictive provisions. Moreover, sample cases from 22nd and 24th legislative terms of the TBMM are examined within the context of political communication, freedom of expression, and ethics. This chapter grounds on a descriptive method based on historical events and legal texts. As a result of the study, it should be stressed that the implementation of “binding group decision” needs to be examined in terms of political ethics as a restrictive element for the freedom of expression and communication, despite being legal.
Keywords: 5. Gender equality; 8. Economic growth; 10. No inequality; 16. Peace & justice